OPERATING SYSTEM LINUX IN OUR SCHOOLS - SZOTKOWSKI, Rene (Trends in education, 2008)
This paper focuses on operating system GNU/Linux and operating system OS MS Windows. It considers closely the comparison of these operating systems in relation to the casual users, students or the pipils at primary.
Keywords: operating system; OS GNU/Linux; OS MS Windows